ANGIOTENSIN II TYPE I RECEPTOR POLYMORPHISM (A1166C AT1R) AS A FACTOR COMPLICATING THE COURSE OF COVID-19 - A.I. Vatsenko; T.I. Koval (Клінічна та профілактична медицина, 2023)
Intriduction: The acute respiratory disease COVID-19 continues to pose a threat to human health worldwide. Identifying new predictors of severe coronavirus disease is necessary to prevent new outbreaks and reduce mortality among the population.